Barriers to pass English teaching professional licensure as perceived by newly graduated Saudi teachers - Alasmari, Nasser (Edelweiss Applied Science and Technology, 2024)
Academicians worldwide constantly question how they can enhance teaching efficiency. Teacher licensure examination has been suggested as a way to achieve this goal. In the same respect, Saudi ministry of education requires prospective teachers to pass Professional licensure exam (PLE) in order to officially enter the teaching job. The present work aimed to give a closer look on this kind of examination as perceived by 23 Saudi candidates holding BA in English and expect to become English teachers. These subjects had a failure experience with taking this exam. Additionally, the use of a semi structured interview, the informants voiced the different kinds of challenges that prevent them from effectively passing this exam. The use of the NVivo software gave results that show the negative attitude these participants hold towards PLE as well as the two categories of obstacles they confronted namely; academic and non- academic.